1012 Examining Daytime Sleepiness, Sleep Apnea, and Cognitive Decline in a 2-year Longitudinal Sample of Cognitively Normal Elderly. (27th April 2018) - Nwade, C; Robbins, R; Seixas, A; Francis, K; Chery, K; Champagne, K; Roseus, J; Madhavaram, S; Rogers, A; Miller, M; Zizi, F; Jean-Louis, G; et al.
Abstract: Introduction: Excessive daytime sleepiness (EDS) has been associated with cognitive decline in the elderly and increased rate of amyloid accumulation. EDS is one symptom of obstructive sleep apnea (OSA), and OSA with EDS is associated with the development of comorbidities. There is an established relationship between OSA and cognitive impairment; however, the role of EDS in this relationship is unknown. Methods: Data from a 2-year prospective longitudinal study that sampled non-depressed, cognitively normal individuals between the ages of 55 to 90 years was used to evaluate the association between OSA severity, EDS, and amyloid deposition measured as longitudinal changes in cerebrospinal (CSF) amyloid beta (Aβ42). Participants completed the Epworth Sleepiness Scale (ESS) questionnaire and home monitoring for assessing apnea-hypopnea index with 3% desaturation or arousal (AHI3a), a marker of OSA severity. CSF Amyloid beta (Aβ42) levels were measured using ELISA. We examined the relationship between change in A β from baseline to follow up and OSA severity (AHI3a) using linear regression models. Results: Mean A β change was 79.37 ± 170.64. Mean AHI3a was 19.22 ± 14.34. Mean response for ESS was 5.75 ± 3.61. Using linear regression, revealed an inverse relationship between A β change and baseline AHI (beta = -44.9, p = .011). When ESS was included in the model, the relationship between OSA severity as a significant predictor of A β was AHI3a: beta = -44.5, p = .019; ESS: beta = -.37.9, p-value =.178); whereas the model was significant with only AHI3a as a predictor (F = 6.7, p = .011). P-values decreased in the model when both AHI3a and ESS were included as predictors (F = 4.3, p = .016). Conclusion: Findings show an inverse association between CSF A β change and OSA severity. Our findings suggest that daytime sleepiness reduces the significance of this relationship when included as a predictor. Future research may examine the relationship between daytime sleepiness and cognitive decline among elderly without OSA to isolate the role of sleepiness in amyloid deposition and cognitive decline. Support (If Any): R01HL118624-01; CTSI UL1TR000038 and K07AG052685.